Our connections to soil health through simile - Alan J. Franzluebbers (Agricultural & Environmental Letters)
Abstract Healthy soil supports the global carbon cycle, the water cycle, and many nutrient cycles to stabilize ecosystems. We take these processes for granted, and yet, disruptions to these cycles would be devastating if soils became defunct and plants could not photosynthesize. As with the health of the human body to which we rely on to carry out our daily lives, so too does the health of soil give essential life to our world. Strong corollaries exist between the functioning of the human body and the soil body. This essay explores these two bodies through simile. Just as we wish others good health, so too should each of us (and society) wish a world with excellent soil health. A foundational pathway laid by strong science, but pitched to engage more of the public in this effort to foster better soil health might be through non‐traditional impressionistic storylines.